A European curriculum for nurses working in haemophilia. (17th August 2015) - ,; Harrington, C.; Bedford, M.; Andritschke, K.; Barrie, A.; Elfvinge, P.; Grønhaug, S.; Mueller‐Kagi, E.; Leenders, B.; Schrijvers, L. H.
Abstract : Introduction: Currently, there is no consensus on education required to develop haemophilia nursing. The aim was to develop a curriculum for haemophilia nurses that could be used as a resource in Europe. This could form a basis for continuous professional development and used in the preparation of specialized educational programmes. Methods: The EAHAD nurses working group set out to describe the skills and knowledge needed for a nurse to work in this specialty. This was considered at two levels: basic requirements and at a more advanced level. The working group acted as a focus group for this project drawing on existing specialist training, national role definitions, competencies and results of the EAHAD Nurses survey (2012). A template was populated with the knowledge base and the skills required. Results: Themes were analysed and information generated organized into domains: content of curriculum; learning outcomes, defined in terms of knowledge, skills, behaviour and attitudes; and suggestions for teaching methods. For curriculum content the following domains were identified: Applied biological science; treatment and management of haemophilia and associated disorders; genetic practice; care management of affected carriers and women; the impact of living with bleeding disorders; evidence base and applied research in haemophilia practice; and, the specialist role of the haemophilia nurse. Examples are given for teaching and learning process. Conclusion: This curriculum is intended for use as a strategic resource to outline education for the haemophilia nurse and contribute to the standardization and benchmarking of haemophilia nursing care and thus to improvement in the quality of patient care.